Power Struggles and Conflict Visibility in Contested Political Forests: A Case Study in Sukaslamet Village, Indramayu Regency, Indonesia - Elvara Dwi Satria; Sudarsono Soedomo; Rina Mardiana (Journal of Natural Resources and Environmental Management)
Forest tenure conflicts have been a problem in Perhutani's management areas for decades. As an entity authorized to manage, exploit, and protect most of the forest areas in Java, Perhutani's forest management is not free from land occupation issues. The duality in viewing land rights between Perhutani from the legal side and the community from the historical side of control is a narrative that continues to be debated and is challenging to resolve. This study aims to describe the local dynamics of forest tenure conflicts through empirical evidence of the historical trajectory of forest tenure in the Perhutani management area in Indramayu. Using a qualitative research method, this study presents case studies of land tenure conflict events within the framework of conflict visibility assessment and the Actor-Centered Power (ACP) approach in its analysis. The results of the conflict visibility assessment show the gradation and historiography of forest tenure conflicts in Perhutanimanaged areas and produce several important findings to complement the forest tenure conflict literature. The research findings show how shifts in actor power led to changes in forest tenure conflicts in Indramayu. Finally, the establishment of the Forest Areas with Special Management policy as an effort to resolve conflicts can cause new contestations by inviting other powerful actors.